Re-Mapping Integrative Competencies at IAIN Kediri: An al-Ghazali Critique - Dodi, Limas; Yusuf, Moh. Asror (LPPM IAIN Kudus, 2025)
This study critically evaluates the concept of integration within Islamic knowledge to formulate a model of integrative competencies for students at IAIN Kediri, using al-Ghazali’s epistemology as a critical instrument. This study applies al-Ghazali’s integrative epistemology to develop student competencies as agents of knowledge integration within Islamic higher education, formulated through learning design and curriculum implementation. Using a qualitative approach, the research draws on primary sources from al-Ghazali’s works, particularly Ihya’ Ulum al-Din, and secondary data from IAIN Kediri’s institutional documents as well as interviews with the academic community of the Faculty of Ushuluddin and Da’wah (FUDA). The findings reveal that FUDA students’ intellectual tradition remains predominantly orthodox and value-oriented, indicating that epistemic integration between religious and modern sciences has yet to be fully achieved. The application of al-Ghazali’s epistemology within the curriculum leads to an integrative competence development model encompassing three dimensions: intellectual-transcendental (mastery of both religious and scientific knowledge in learning outcomes), social-ethical (the practical application of knowledge for public benefit as reflected in course outputs), and moral-axiological (the formation of character and social responsibility through student community engagement). Al-Ghazali’s integrative framework introduces a new paradigm in the design of integrative curricula, in which both religious and general education are grounded in the concept of living tauhidi (monotheism), the belief in God as the ultimate source of knowledge, supported by three integrative pillars: revelation, ethics, and social engagement. This foundation is contextualized within modern pedagogical goals, materials, and methods that are responsive to contemporary educational challenges.